The Importance of Free Economic Zones in Central Asia. (Texas Journal of Multidisciplinary Studies, 2022)
The process of globalization, erasing the boundaries in the promotion of goods and services, also erases the boundaries of competition between countries. If earlier countries competed within their region or continent, then in the context of accelerating globalization, commodity producers in any country have to compete with producers from almost the rest of the world. As a result, developing countries are heavily influenced by competition from more developed countries. The global financial and economic crisis has further intensified competition at the global level. Cases of dumping have become more frequent, many countries have begun to pursue a more aggressive competitive policy in the struggle to attract foreign capital. The following article is devoted to the study of few economic zones in Central Asia